Context-related drivers, occurrence and human exposure to antibiotic resistant Campylobacter in selected river systems in the Eastern Cape, South Africa - Chibwe, Mary (Rhodes University, Faculty of Science, Institute for Water Research)
The increasing prevalence of antibiotic-resistant Campylobacter species in river systems is a growing public health concern globally. This challenge presents the need to understand the drivers influencing the occurrence of these antibiotic-resistant strains to inform effective mitigation strategies. Identifying local anthropogenic pressures/activities will enable tailored intervention and ensure that management efforts are targeted and effective in mitigating actual risks faced by local water resources. In particular, the occurrence of antibiotic-resistant Campylobacter in river systems causes concerns regarding potential human exposure. Campylobacter species are regularly implicated in both animal and human diarrhoea, and have gained recognition as one of the main causes of waterborne diseases. This study investigated context-related drivers to the presence of antibiotic-resistant Campylobacter, its occurrence, and the risk of human exposure in the Bloukrans and Swartkops rivers in the Eastern Cape, South Africa. The study utilised a questionnaire survey and focus group discussions to identify context-related sources and drivers of antibiotic-resistant bacteria and genes in the Bloukrans and Swartkops rivers. Additionally, physico-chemical analysis of water samples was done, and polymerase chain reaction (PCR) was employed to investigate occurrences of Campylobacter in both rivers, as well as the presence of virulent and antibiotic-resistant genes. Two control sites, one for each river, and a total of nine other sampling sites were selected for this study, four along the Bloukrans River and five along the Swartkops River. Water samples were collected from all eleven sites over a period of one year, covering all the seasons (winter, spring, summer and autumn). Exposure assessment was investigated by conducting propidium monoazide-quantitative polymerase chain reaction (PMA-qPCR) to quantify the concentration of viable Campylobacter and its antibiotic-resistance genes (ARGs) in the river water. The calculated concentration of viable Campylobacter and ARGs was then used to estimate human exposure dose of antibiotic-resistant Campylobacter via unintentional ingestion during swimming in the Bloukrans or Swartkops rivers. The questionnaire surveys and focus group discussions identified the factors of socio-demographic characteristics of the study catchments, lack of knowledge regarding antibiotic resistance, inappropriate antibiotic and disposal practices as well as anthropogenic activities (improper solid waste management, discharge of poorly treated wastewater, poor animal husbandry practices, urban run-off and storm water, industrial effluent and agricultural run-off) as context-related sources and drivers contributing to the emergence and of continuing occurrence antibiotic-resistant bacteria and genes in the Bloukrans and Swartkops rivers. The results obtained in this study suggest that the physiochemical properties of the water in the Bloukrans and Swartkops rivers are conducive for Campylobacter survival. The prevalence of Campylobacter was high at sites that recorded high turbidity, low dissolved oxygen and high conductivity. This study also highlighted the widespread and continual presence of Campylobacter spp. in the Bloukrans and Swartkops rivers, which are potentially antibiotic-resistant. The prevalence of Campylobacter was 60% virulence genes were detected at 15% (cadF), 10% (htrB), 10% (clpP), 5% (ciaB) and 5% (ctdC) for water samples from the Bloukrans River. Campylobacter was detected in 58% of water samples from the Swartkops River, while cadF, htrB, ciaB, clpP and ctdB were detected at 24%, 0%, 9.5%, 14.8% and 4.8%, respectively. Of the Campylobacter-positive water samples, the virulence genes cmeA, cmeB and cmeC were detected in 20%, 65% and 10% of the water samples from Bloukrans River, respectively. Similarly, the genes cmeA, cmeB and cmeC were detected at 14.3%, 52% and 9.5%, respectively, for the Swartkops River. Tetracycline resistance genes (tetO) were detected in 70% and 76% of the water samples collected from the Bloukrans and Swartkops rivers, respectively. It was also observed that the sampling site had a significant effect on the detection of Campylobacter for both rivers (p < 0.05). The prevalence of Campylobacter was higher for sites impacted by anthropogenic activities. The results show that sampling season had no significant effect on the occurrence of Campylobacter for both rivers. The analysis through PMA-qPCR revealed that the mean concentrations of the Campylobacter 16S rRNA gene from viable cells ranged from 2.1 Ã— 104 to 1.75 Ã— 105 copies/ml for the Bloukrans River, and from 0 (no detection) to 1.11 Ã— 104 copies/ml (viable concentration) for the Swartkops River. The concentration of tetO from viable cells ranged from 4.75 Ã— 101 to 2.71 Ã— 103 copies/ml and 115.96 to 325.12 copies/ml, for the Bloukrans and Swartkops Rivers, respectively. Similarly, the concentration of cmeB genes from viable cells ranged from 7.8 Ã— 101 to 2.76 Ã— 104 copies/ml for the Bloukrans River and from 1.71 Ã— 101 to 7.39 Ã— 103 copies/ml for the Swartkops River. We utilized the calculated concentrations of viable Campylobacter 16S rRNA genes and ARGs to estimate the human intake burden of viable Campylobacter 16S rRNA copies per one-hour of swimming to range from 9.9 Ã— 101 "“ 3.7 Ã— 106 copies/h across the two rivers. The human intake burden of Campylobacter ARGs ranged from 3.6 Ã— 102 "“ 5.8 Ã— 105 copies/h for cmeB, and 9.98 Ã— 102 "“ 5.7 Ã— 104 copies/h for tetO. This study highlighted the intricate interplay of socio-demographic characteristics in the study catchments, such as insufficient awareness of antibiotic resistance, inappropriate antibiotic disposal practices and anthropogenic activities, which all contribute to the prevalence of antibiotic-resistant Campylobacter in the Bloukrans and Swartkops rivers, emphasizing the need for targeted interventions to address these specific influences. There is a potential risk of Campylobacter infections associated with human exposure to the rivers. This work contributes towards the body of knowledge in closing the current research gap on possible human exposure to antibiotic-resistant Campylobacter, and in general, exposure to ARBs through freshwater sources. The findings have practical implications for designing targeted interventions to mitigate these risks, to enhance the overall environmental and public health management in the region.
Keywords: Antibiotic resistance; Campylobacter; Health risk assessment; Drug resistance; Public health -- South Africa -- Eastern Cape; Polymerase chain reaction